Exogenous abscisic acid application decreases cadmium accumulation in Arabidopsis plants, which is associated with the inhibition of IRT1-mediated cadmium uptake - Fan, Shi Kai; Fang, Xian Zhi; Guan, Mei Yan; Ye, Yi Quan; Lin, Xian Yong; Du, Shao Ting; Jin, Chong Wei (Frontiers in Plant Science, 2014)
Cadmium (Cd) contamination of agricultural soils is an increasingly serious problem. Measures need to be developed to minimise Cd entering the human food chain from contaminated soils. We report here that, under Cd exposure condition, application with low doses of (0.1–0.5 μM) abscisic acid (ABA) clearly inhibited Cd uptake by roots and decreased Cd level in Arabidopsis wild-type plants (Col-0). Expression of IRT1 in roots was also strongly inhibited by ABA treatment. Decrease in Cd uptake and the inhibition of IRT1 expression were clearly lesser pronounced in an ABA-insensitive double mutant snrk2.2/2.3 than in the Col-0 in response to ABA application. The ABA-decreased Cd uptake was found to correlate with the ABA-inhibited IRT1 expression in the roots of Col-0 plants fed two different levels of iron. Furthermore, the Cd uptake of irt1 mutants was barely affected by ABA application. These results indicated that inhibition of IRT1 expression is involved in the decrease of Cd uptake in response to exogenous ABA application. Interestingly, ABA application increased the iron level in both Col-0 plants and irt1 mutants, suggesting that ABA-increased Fe acquisition does not depend on the IRT1 function, but on the contrary, the ABA-mediated inhibition of IRT1 expression may be due to the elevation of iron level in plants. From our results, we concluded that ABA application might increase iron acquisition, followed by the decrease in Cd uptake by inhibition of IRT1 activity. Thus, for crop production in Cd contaminated soils, developing techniques based on ABA application potentially is a promising approach for reducing Cd accumulation in edible organs in plants.